Pengaruh penanaman modal dalam negeri, upah minimum dan belanja modal terhadap daya serap tenaga kerja di Provinsi Jambi - Kenraraswati, Rizki; Hidayat, M. Syurya; Amzar, Yohanes Vyn (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
The study aims to analyze the effect of domestic investment (PMDN), minimum wage (UMP) and capital expenditure (BM) on employment absorption in Jambi Province. The data used is time series data of Jambi Province during the period 2000-2016. Data were analyzed descriptively as well as multiple regression models. The results of the study found that: 1) the average growth of employment is 3.11percent per year, domestic investment is 11.67 percent per year, UMP is 16.44 percent per year and capital expenditure is 20.00 percent per year; 2) Simultaneously PMDN, UMP and BM have a significant effect on employment in Jambi Province. Partially the BM variable does not have a significant effect while the PMDN and UMP variables have a significant effect on employment in Jambi Province.